Presidential economic approval rating and the cross-section of stock returns - Chen, Zilin; Da, Zhi; Huang, Dashan; Wang, Liyao (Journal of Financial Economics, 2023)
We construct a monthly presidential economic approval rating (PEAR) index from 1981 to 2019, by averaging ratings on the president’s handling of the economy across various national polls. In the cross-section, stocks with high betas to changes in the PEAR index significantly under-perform those with low betas by 1.00% per month in the future, on a risk-adjusted basis. The low PEAR beta premium persists up to one year, and is present in various sub-samples and even in other G7 countries. PEAR beta dynamically reveals a firm’s perceived alignment to the incumbent president’s economic policies and investors seem to misprice such an alignment.